Strategy for developing the utilization of organic waste as an alternative source of electricity in Indonesia - Yuniar, Farchani Putri; Ginting, Grace Gardania (Bioculture Journal, 2024)
Background: Indonesia has pledged to reach its Net Zero Emission target by 2060, necessitating the shift to renewable energy sources. To achieve this, Indonesia must transition from its current reliance on fossil fuel power plants to renewable energy generators, ensuring the same or greater electricity capacity. One viable renewable energy source is organic waste. This study aims to explore strategies for developing organic waste as an alternative energy source to bolster Indonesia's energy resilience and environmental sustainability. Method: The research employs a qualitative approach, including literature reviews and qualitative descriptive analysis. Findings: Waste to Energy (WtE) processes convert waste into electricity and/or heat, aiding in greenhouse gas reduction, improving waste management efficiency, and supporting sustainable development. WtE technologies can utilize both thermochemical and biochemical methods to convert waste into energy. The Indonesian government is known to have 12 projects to accelerate the installation of Waste Processing into Electrical Energy, both the Waste Power Plants that have been in operation and under construction and using gasification as the method. The development of WtE faces various challenges ranging from completeness and consistency of regulations, high tipping fees, complex cooperation mechanisms and business models, problems with the characteristics and nature of Indonesian waste that need special handling, and rejection from residents. Conclusion: Strategies that can be implemented in developing WtE in Indonesia include drafting policies and regulations, increasing public awareness, collaboration with the private sector, choosing the right technology, developing infrastructure, increasing the efficiency of waste collection, and international partnerships.  Novelty/Originality of this study: This research offers concrete strategies to develop Waste to Energy (WtE) technology in Indonesia, including policy formulation, increasing public awareness, and collaboration with the private sector to utilize organic waste as a renewable energy source to support the 2060 Net Zero Emission target.